Training needs of input dealers on pesticidal application on cotton crop in Punjab - M.K. Sarda,; S.S. Gill, (Journal of Agricultural Extension Management, 2025)
Cotton (Gossypium Sp.) 'White Gold' is a premier textile fibre crop and also the second most important non-conventional oilseed in the world. Punjab is one of the major cotton producing states in India and produces about one fifth of the total cotton in the country. Over ninety five per cent of the area is in the cotton belt which includes districts of Bathinda, Faridkot, Ferozepur, Mansa and Sangrur